Te Aho o Te Kahu: weaving equity into national-level cancer control. Issue 9 (September 2022) - Mako, Michelle; Gurney, Jason; Goza, Moahia; Ruka, Myra; Scott, Nina; Thompson, Gary; Sarfati, Diana
Summary: The purpose of this manuscript was to consider how mainstream health organisations can develop structures, processes, and functions to address inequity, using the New Zealand Cancer Control Agency ( Te Aho o Te Kahu ) as an example. In New Zealand ( Aotearoa ), as in other countries, inequities in cancer incidence and outcomes exist between population groups, including for indigenous populations. Despite much discussion regarding the need to address racial inequities, often the proposed solutions are at operational or programmatic levels, and disadvantaged communities are unable to have much of a say in the system design and service delivery of these solutions. The establishment of a dedicated cancer control agency has created a unique opportunity to centralise principles and approaches to achieving equity within the core functions of the agency, and enabled a new method of approaching cancer control with the aim of achieving equity for the most disadvantaged populations. Using a framework based on the founding agreement between New Zealand's Indigenous Māori people and the British Government ( Te Tiriti o Waitangi ), we consider how health system organisations can develop structures, processes, and functions to achieve equity, and summarise how this new agency has been shaped to achieve these objectives for Māori people in particular, including the innovative and equity-first approach to organisational structure and focus. Within this framework, we highlight the key equity-focused work programmes, initiatives, and other actions taken since the inception of the agency. Finally, we discuss the ongoing equity-related challenges the agency faces, as well as the current and future opportunities for achieving equity in health outcomes.